Bioenergy crop greenhouse gas mitigation potential under a range of management practices. Issue 2 (7th March 2014) - Hudiburg, Tara W.; Davis, Sarah C.; Parton, William; Delucia, Evan H.
Abstract Perennial grasses have been proposed as viable bioenergy crops because of their potential to yield harvestable biomass on marginal lands annually without displacing food and to contribute to greenhouse gas (GHG) reduction by storing carbon in soil. Switchgrass, miscanthus, and restored native prairie are among the crops being considered in the corn and agricultural regions of the Midwest and eastern United States. In this study, we used an extensive dataset of site observations for each of these crops to evaluate and improve the DayCent biogeochemical model and make predictions about how both yield and GHG fluxes would respond to different management practices compared to a traditional corn‐soy rotation. Using this model‐data integration approach, we found 30–75% improvement in our predictions over previous studies and a subsequent evaluation with a synthesis of sites across the region revealed good model‐data agreement of harvested yields (r2 > 0.62 for all crops). We found that replacement of corn‐soy rotations would result in a net GHG reduction of 0.5, 1.0, and 2.0 Mg C ha−1 yr−1 with average annual yields of 3.6, 9.2, and 17.2 Mg of dry biomass per year for native prairie, switchgrass, and miscanthus respectively. Both the yield and GHG balance of switchgrass and miscanthus were affected by harvest date with highest yields occurring near onset of senescence and highest GHG reductions occurring in early spring before the new crops emergence. Addition of a moderate length rotation (10–15 years) caused less than a 15% change to yield and GHG balance. For policy incentives aimed at GHG reduction through onsite management practices and improvement of soil quality, post‐senescence harvests are a more effective means than maximizing yield potential.